CD44 variant exons induce chemoresistance by modulating cell death pathways - Yanova, Maria; Stepanova, Evgeniya; Maltseva, Diana; Tonevitsky, Alexander (Frontiers in Cell and Developmental Biology, 2025)
Cancer chemoresistance presents a challenge in oncology, often leading to treatment failure and disease progression. CD44, a multifunctional cell surface glycoprotein, has garnered attention for its involvement in various aspects of cancer biology. Through alternative splicing, CD44 can form isoforms with the inclusion of only standard exons, typical for normal tissue, or with the addition of variant exons, frequently expressed in cancer tissue and associated with chemoresistance. The functions of CD44 involved in regulation of cancer signaling pathways are being actively studied, and the significance of specific variant exons in modulating cell death pathways, central to the response of cancer cells to chemotherapy, begins to become apparent. This review provides a comprehensive analysis of the association of CD44 variant exons/total CD44 with clinical outcomes of patients undergoing chemotherapy. The role of CD44 variant exons v6, v9 and others with a significant effect on patient chemotherapy outcomes by means of key cellular death pathways such as apoptosis, ferroptosis and autophagy modulation is further identified, and their impact on drug resistance is highlighted. An overview of clinical trials aimed at targeting variant exon-containing isoforms is provided, and possible directions for further development of CD44-targeted therapeutic strategies are discussed.